A comparative economics of natural farming and conventional farming of rice cultivation in Arunachal Pradesh - Athawale, Snehal; Singh, Ram; Hatai, Lakshmi Dhar; Sing Bey, Brota; Singh, N. Anandkumar; Singh, Rajkumar Josmee; Hemochandra, L. (ORYZA-An International Journal of Rice, 2024)
The study was conducted in the state of Arunachal Pradesh, East Siang district was purposively selected due to its reliance on agriculture as the primary livelihood with rice being the main crop. Primary data was collected from 45 respondents each from natural and conventional farming making the sample total 90, for the year 2022-23 of kharif season. The growth rate in area, production and productivity at the world, India, East Siang district as well as state of Arunachal Pradesh were found to be positive. Significance difference was observed on cost of bullock labour, machine labour, seeds and plant protection in natural farming. The total cost of rice cultivation was lower in natural farming by 29.49 per cent. Although the yield and gross returns was lower in natural farming but the net returns was significantly higher than conventional farming by mean difference of ? 6119.78 per hectare. The study also highlights potential gender-based variations in labor requirements, observing natural farming as labour intensive farming. In both natural and conventional farming, the per cent of total female labour utilization was observed to be higher than total male labour.